Sectoral system of innovation in payment service of Vietnam: preliminary assessments - Minh, Dinh Tuan; Lien, Nguyen Thuy (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Objectives of this study are to apply the approach of sectoral system of innovation to make preliminary views on the status of the innovation system in finance-banking sector of Vietnam for payment service. The study applies the use of questionnaires and in-depth interviews with experts and representatives of some organizations in finance-banking sector. The study shows the system of institutions and policies plays the important roles, seemly in the top rank, in promotion of innovation activities related to payment service. Besides, clients come to appear as a crucial factor to push up investment efforts of these organizations for innovation activities. Also, the leading roles of commercial banks and Fintech companies are rising as new actors to push up innovation activities in this sector. Code: 19121004